1. The problem statement, all variables and given/known data Find General Solution: y"+6y'+9y=e-3x-27x2 2. Relevant equations 3. The attempt at a solution I know you have yh which is the general solution to the left side of the equation set to 0 and then fine the particular solution. When i try to find yp1 I get yp1=Ae-3x, y'p1=-3Ae-3x, and y"p1=9Ae-3x Substituting that into the left side we get 9Ae-3x+6(-3Ae-3x)+9(Ae-3x)=Ae-3x Canceling out Ae-3x we get 9A-18A+9A=1 0A=1 SO does this mean when i'm finding the general solution y=yh+yp1+yp2 that yp1 is gonna be 0? I Know this is a very simple question but my mind is running in circles!